Konsep Sakinah dalam Perkawinan: Sebuah Tinjauan Hukum Islam dan Psikologi - Nur Faizah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
The concept of Sakinah in marriage is the foundation for harmony and tranquility in family members' relationships. This article explores the idea of Sakinah from Islamic law and psychology perspectives, and the integration between the two in understanding and building a harmonious family. From the perspective of Islamic law, the concept of Sakinah is based on Islamic teachings that regulate the rights and obligations of family members and offer solutions in conflict resolution. Meanwhile, from a psychological perspective, the concept is understood as the result of psychological dynamics within the family, including interaction, communication, and parenting styles. The integration between the perspectives of Islamic law and psychology is important to strengthen religious values in everyday family life and to understand the psychological factors that support the creation of a Sakinah and harmonious family. This holistic understanding is expected to guide individuals and families in building harmonious and happy relationships between family members by Islamic teachings and psychological principles.